Short-Term Efficacy in Polypoidal Choroidal Vasculopathy Patients Treated With Intravitreal Aflibercept or Conbercept - Xue, Yin; Qinhua, Cai (Frontiers in Medicine, 2022)
Purpose.To compare the short-term efficacy in polypoidal choroidal vasculopathy (PCV) patients treated using either aflibercept or conbercept. Methods. This prospective study included forty-one treatment-naive PCV patients (42 eyes) finally. All patients were treated with either aflibercept or conbercept using an initial series of 3 monthly loading injections. Changes in the best-corrected visual acuity (BCVA) and anatomic outcomes were evaluated at 3 months. Results. BCVA was improved with reduction in central choroidal thickness (CCT), central foveal thickness (CFT) and subretinal fluid (SRF) after 3-loading injection in both IVA and IVC groups. There was no significant difference in either visual or anatomic outcomes between the two groups 3 months later. However, compared with IVC group, significant visual improvement was observed in PCV patient in IVA group with baseline BCVA (LogMAR) <1.0. Visual outcome improved ≥3 lines in 13 patients of IVA group (59%), while 9 patients in IVC group (45%). Meanwhile, a relatively higher proportion of polyp regression was observed in IVA group (63%) compared with IVC group (55%). Conclusions. Visual and anatomic outcomes were significantly improved in both IVA and IVC groups, but it is suggested a potential superior short-term response in IVA group.